Mouse models illuminate MAIT cell biology. (February 2021) - Wang, Huimeng; Chen, Zhenjun; McCluskey, James; Corbett, Alexandra J
Highlights: MAIT cells recognise vitamin-B based antigens presented on MR1. MAIT cells are present at lower frequencies in mice than in humans. MAIT cell deficient strains and mice with increased MAIT cells have been developed. Mouse models demonstrate important roles for MAIT cells in protective immunity, autoimmunity and cancer. Abstract: The field of mucosal-associated invariant T cell (MAIT) biology has grown rapidly since the identification of the vitamin-B-based antigens recognised by these specialised T cells. Over the past few years, our understanding of the complexities of MAIT cell function has developed, as they find their place among the other better known cells of the immune system. Key questions relate to understanding when MAIT cells help, when they hinder or cause harm, and when they do not matter. Exploiting mouse strains that differ in MAIT cell numbers, leveraged by specific detection of MAIT cells using MR1-tetramers, it has now been shown that MAIT cells play important immune roles in settings that include bacterial and viral infections, autoimmune diseases and cancer. We have also learnt much about their development, modes of activation and response to commensal microbiota, and begun to try ways to manipulate MAIT cells to improve disease outcomes. Here we review recent studies that have assessed MAIT cells in models of disease.